The consumer has spoken: Patient experience is now healthcare's core differentiator - Jason Wolf (The Beryl Institute, 2018)
In just a few days we will celebrate Patient Experience Journal's (PXJ) 4th anniversary since our inaugural publication. In these 4 short and quick years we have seen 163 articles published in our first four volumes that have stirred a significant focus on building the evidence base in patient experience. Not only has PXJ served as the central clearing house for thoughtful research, measurable cases, and insightful narratives, but it also has reinforced the breadth and depth of what patient experience truly encompasses. This integrated view was reinforced by the very voices of healthcare's consumers in The Beryl Institute's recent study on Consumer Perspectives of Patient Experience in which participants reveal experience is extremely important to them, focuses on individual health, is grounded in an individual's desire to be acknowledged and is identified as a key driver for healthcare decision-making. It is for this reason experience is found to be a critical differentiator in healthcare now and into the future. And it is on this foundation that the patient experience movement continues to grow, commitment continues to expand and the contributions of PXJ continue to push the boundaries of our overall conversation. That is the essence of our strength, that we find not only on these pages, or in the words of our many contributors, but also in the voices of all who are impacted by or part of the global healthcare ecosystem. There are few other efforts as honorable than to ensure the best for your fellow human being. In our rigor to push the edges of this conversation, we will continue to thrive together.